Dowling-Degos Disease and Hidradenitis Suppurativa. Epidemiological and Clinical Study of 15 Patients and Review of the Literature - Eugenia Agut-Busquet; Iris González-Villanueva; Jorge Romani Gabriel; Jose Carlos Pascual; Miquel Ribera Pibernat; Jesús Luelmo (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)